Spread of Fukushima‐derived radiocesium over the coastal ocean in response to typhoon‐induced flooding in September 2011. Issue 5 (22nd March 2022) - Tanaka, Kiyoshi; Nagao, Seiya; Kitade, Yujiro; Niki, Masato; Katsumata, Takaaki; Miyama, Toru; Yoshinari, Hiroshi
Abstract: The Tohoku earthquake off the Pacific coast of Japan on 11 March 2011 and the resulting tsunami led to severe damage to the Fukushima Daiichi Nuclear Power Plant (FDNPP) in Japan. Therefore, a shipboard survey was conducted to elucidate spread processes of radioactive cesium over the coastal ocean in the Kuroshio–Oyashio transition zone (south of the FDNPP) from 07 to 12 September 2011, that is, within 8 d of a river flood event associated with Typhoon Talas (T1112). In the survey, broad distributions of radiocesium and low‐salinity water extending nearly 100 km off the coast were successfully observed at the sea surface. Moreover, a significant negative correlation was detected between radiocesium and salinity in the coastal ocean. Just before the shipboard survey, the typhoon brought extremely heavy rainfall over the catchment areas of the Tone and Naka Rivers flowing into the survey region, resulting in discharges from the Tone and Naka Rivers reaching approximately 2800 and 700 m 3 s −1, respectively, at their peaks (04 September). These discharges were the highest recorded since 2007. Satellite images corresponding to the high‐radioactivity and low‐salinity areas revealed that chlorophyll blooms also spread over a broad area during the survey. These results indicate that the broad distributions of radiocesium and low‐salinity water over the coastal ocean were brought about by the high levels of river discharge associated with the typhoon.